2022
DOI: 10.1039/d2dt00772j
|View full text |Cite
|
Sign up to set email alerts
|

Toward asymmetric aziridination with an iron complex supported by a D2-symmetric tetra-NHC

Abstract: A macrocyclic C2-symmetric tetra-NHC iron(ii) complex was synthesized and tested for asymmetric aziridination between aryl azides and alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…(See ligands depicted in Scheme S2). [25,[35][36][37] Jenkins and coll. showed that these systems exhibit interesting nitrene transfer activities but need to operate at temperatures ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(See ligands depicted in Scheme S2). [25,[35][36][37] Jenkins and coll. showed that these systems exhibit interesting nitrene transfer activities but need to operate at temperatures ca.…”
Section: Introductionmentioning
confidence: 99%
“…Pursuing our quest for efficient aziridination catalysts, our attention was attracted by the Fe complexes of tetracarbene macrocyclic ligands reported by the groups of Jenkins, Kühn and Meyer. (See ligands depicted in Scheme S2) [25,35–37] . Jenkins and coll.…”
Section: Introductionmentioning
confidence: 99%
“…70 The obtained silver complexes can subsequently be treated with an iron halide and the formed silver halide be removed by filtration over Celite to receive the respective iron complexes. 69,70…”
Section: Complex Synthesismentioning
confidence: 99%
“…Generally speaking, it has to be pointed out, that the aziridination of alkenes with organic azides at these conditions already proceeds without an iron complex in low (2%) up to moderate yields (60%). 64,65,69,103,235,236 In extreme cases, this can make Scheme 32 Aziridination of olefins with organic azides catalyzed by 8, 16, 17 and 62.…”
Section: Aziridinationmentioning
confidence: 99%
“…11 Tuning of its electronic properties by insertion of substituents varying the NHC backbone affects not only catalyst stability but also its activity, emphasising once more the role of ligand design. 12 Pioneering work on bio-inspired non-heme macrocyclic iron tetra(NHCs) has been done by Jenkins et al [13][14][15][16][17][18] , Meyer et al [19][20][21] and our group. 12,[22][23][24][25][26] During these studies several bridged tetra(imidazole-2-ylidene) iron complexes have been prepared and characterised (Fig.…”
mentioning
confidence: 99%